2018
DOI: 10.1007/s10549-018-4768-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of reproductive history with breast tissue characteristics and receptor status in the normal breast

Abstract: IntroductionReproductive history has been associated with breast cancer risk, but more knowledge of the underlying biological mechanisms is needed. Because of limited data on normal breast tissue from healthy women, we examined associations of reproductive history and established breast cancer risk factors with breast tissue composition and markers of hormone receptors and proliferation in a nested study within the Karolinska Mammography project for risk prediction for breast cancer (Karma).Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 43 publications
8
25
2
2
Order By: Relevance
“…We report inverse associations of breastfeeding duration with the proportion of fat tissue. Consistent with our ndings, Gabrielson et al found inverse associations, though only marginally signi cant associations of breastfeeding with the percentage of adipose tissue in the breast (β= -0.55, p = 0.05) [20]. Studies on breast tissue remodeling after lactation in humans are very limited though some studies suggest that the protective effect of breastfeeding on breast cancer risk may be related to the increased cellular proliferation and epithelial exfoliation of breast tissue during lactation with subsequent apoptosis after discontinuation of breastfeeding that could result in elimination of cells which may have DNA damage [4,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We report inverse associations of breastfeeding duration with the proportion of fat tissue. Consistent with our ndings, Gabrielson et al found inverse associations, though only marginally signi cant associations of breastfeeding with the percentage of adipose tissue in the breast (β= -0.55, p = 0.05) [20]. Studies on breast tissue remodeling after lactation in humans are very limited though some studies suggest that the protective effect of breastfeeding on breast cancer risk may be related to the increased cellular proliferation and epithelial exfoliation of breast tissue during lactation with subsequent apoptosis after discontinuation of breastfeeding that could result in elimination of cells which may have DNA damage [4,[31][32][33][34].…”
Section: Discussionsupporting
confidence: 92%
“…We also report, for the rst time, a greater proportion of stroma in nulliparous women and an inverse association of number of children in parous women with proportion of stroma. Consistent with our ndings for epithelium, a recent study by Gabrielson et al of core-biopsy samples of normal breast tissue from 153 cancer-free women found a greater proportion of epithelium in parous as compared to nulliparous women (parous vs. nulliparous β = 0.56, p = 0.07) [20]. In contrast, an earlier study by Gertig et al within NHS, found no associations of parity with proportion of epithelium or stroma.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations